The effect of positive thinking training on anxiety and happiness among older adults: A quasi-experimental study - Anis Pourdavarani; Jamileh Farokhzadian; Mansooreh Azizzadeh Forouzi; Sedigheh Khodabandeh Shahraki (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Anxiety and depression are the most prevalent mental disorders associated with aging. Positive thinking training is a way to help older adults cope with anxiety and depression and increase their happiness. This study aimed to determine the effect of positive thinking training on anxiety and happiness among older adults. MATERIALS AND METHODS: This quasi-experimental study was conducted with 48 older adults referred to two comprehensive health service facilities in the southeastern Iranian province of Kerman. The intervention (n = 24) and control (n = 24) groups were randomly assigned from a convenience sample of older adults. The intervention group attended eight two-hour training sessions on positive thinking. Data were collected before and one month after the positive thinking training using Beck Anxiety Inventory and Oxford Happiness Inventory. All statistical procedures were performed in SPSS software (version 22), with the significance level set to P = 0.05. RESULTS: Before the positive thinking program was delivered, the mean anxiety scores in the intervention and control groups were 13.98 ± 8.61 and 19.25 ± 11.67, respectively. After the intervention was completed, the mean scores for the intervention and control groups were 4.50 ± 4.07 and 15.54 ± 9.04, indicating a significant reduction in anxiety among intervention group participants (t = -5.45, P < 0.001). The mean baseline happiness scores in the intervention and control groups were 26.58 ± 12.40 and 37.91 ± 5.57, respectively, which changed to 62.91 ± 4.66 and 35.62 ± 10.62 at the post-test. Positive thinking training improved happiness in a significant manner (t = -4.08, P < 0.001). CONCLUSION: Results revealed that positive thinking training decreased anxiety and enhanced happiness among older adults. Given the growing elderly population, clinical managers, clinical specialists, nurses in health care centers, and those involved in elderly care facilities can benefit from this non-pharmacological treatment program for older adults suffering from anxiety and depression. It is suggested that preventive programs based on positive psychology be developed to aid in the prevention of people's declining happiness and increasing anxiety as they age.